2008
DOI: 10.1103/physrevb.78.054423
|View full text |Cite
|
Sign up to set email alerts
|

Predicted defect-induced vortex core switching in thin magnetic nanodisks

Abstract: We investigate the influence of artificial defects ͑small holes͒ inserted into magnetic nanodisks on the vortex core dynamics. One and two holes ͑antidots͒ are considered. In general, the core falls into the hole; but, in particular, we would like to note an interesting phenomenon not yet observed, which is the vortex core switching induced by the vortex hole interactions. It occurs for the case with only one hole and for very special conditions involving the hole size and position as well as the disk size. An… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 28 publications
0
26
0
1
Order By: Relevance
“…(10) with the force, F = M vẍ , given by F = −∇V eff . Simulations have revealed the richness of such dynamics, including the possibility of vortex core reversal (switching) triggered by vortex-hole interaction [33]. .…”
Section: Conclusion and Prospectsmentioning
confidence: 99%
“…(10) with the force, F = M vẍ , given by F = −∇V eff . Simulations have revealed the richness of such dynamics, including the possibility of vortex core reversal (switching) triggered by vortex-hole interaction [33]. .…”
Section: Conclusion and Prospectsmentioning
confidence: 99%
“…In more general grounds, it is known that a spin vacancy in 2D nearly classical isotropic magnets generates an interaction potential that attracts the skyrmion center [10][11][12] . Hence, in these magnets containing a low impurity density, such potential allows a vacancy to be at the skyrmion center (similarly, these kind of defects also attract the vortex center in easy-plane magnets 13 and magnetic nanodisks [14][15][16][17] ). Particularly, in easy-plane magnets, a low concentration of nonmagnetic impurities has a strong influence on the Berezinskii-Kosterlitz-Thouless (BKT ) transition temperature 18 and in magnetic nanostructures they generate the physical mechanism behinds the experimental observation of the Barkhauser effect 19,20 .…”
Section: Introductionmentioning
confidence: 99%
“…Equation (2) describes the ith component of the electric field induced by spin-motive force [5][6][7][8][9][10][11]13]: (2) where A s is the vector potential, V s is the scalar potential, m is the unit vector of magnetization, and ± stands for spin-up and spin-down bands. When we calculate the electric field using Eq.…”
Section: Resultsmentioning
confidence: 99%
“…However, vortex gyration is generally a periodic function of time; thus, the time-averaged electric field caused by spin-motive force will be zero, which makes it difficult to detect using DC measurements. Recently, Silva et al showed the possibility of breaking the periodicity of vortex gyration by introducing defects (small holes) via a vortex core reversal in a nanodisk [13]. When a vortex core undergoes a modified gyroscopic motion from the introduction of defects, it is possible to obtain a non-zero DC electric field, which opens a way to detecting spin-motive force.…”
Section: Introductionmentioning
confidence: 99%